Effect of ambient pressure on laser welding of AlSi10Mg fabricated by selected laser melting. (March 2022) - Chen, Nannan; Wan, Zixuan; Wang, Hui-Ping; Li, Jingjing; Yang, Baixuan; Solomon, Joshua; Carlson, Blair
Graphical abstract: Highlights: Increased recoil pressure was mainly responsible for the increase in weld penetration when decreasing ambient pressure. Reduced porosity ratio was resulted from the high ambient pressure which limited pore growth. Large-sized pores were formed by merging small pores, revealed by the high-speed imaging. High ambient pressure reduced the pore size by inhibiting the pore growth and reducing the frequency of merging behavior. Abstract: This work attempted to introduce high pressure to reduce pore generation in laser welding of selective laser melted AlSi10Mg, which is different from the traditional approach where the vacuum was preferred in laser welding of aluminum alloys. To understand these phenomena, the impacts of laser welding parameters and ambient pressure on the porosity and weld geometry were examined. Porosity ratio was found linearly increasing with the laser power or linear energy. High-speed imaging revealed that the large pores were formed by multiple merging of small pores, which explained the decrease in fine porosity (<20 μm) but increase in coarse porosity (50–100 μm) when increasing laser power or linear energy. The vacuum ambiance significantly enlarged the pores (up to ∼400 μm) and formed narrow and deep welds. As pressure increased from 0.1 MPa to 0.4 MPa, the porosity ratio was dramatically decreased from ∼10.2% to ∼2.3% accompanied by a decline in porosity size and weld penetration depth. Numerical simulation results revealed that the shallowed weld penetration under high-pressure ambiance was attributed to the decreased recoil pressure, and the reduced porosity ratio was resulted from the high pressure which limited pore growth and merging.